2021
DOI: 10.1155/2021/7782963
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Inhibits Non-Small-Cell Lung Cancer by Inactivating WNT/β-Catenin Signaling through Downregulating miR-15-5p

Abstract: Background. Nobiletin is a natural compound with anticancer activity; however, the mechanism is not clear. Methods. The inhibitory effect of nobiletin on non-small-cell lung cancer (NSCLC) cells was examined using soft agar, Transwell, and apoptosis analyses. Cancer stemness was measured by sphere assay. Genes and miRNAs regulated by nobiletin were identified by whole-genome sequencing. Protein levels were detected by western blot and immunofluorescence assays. Results. Nobiletin significantly inhibited NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…LiCl partially reversed the decrease in cell proliferation, invasion, and migration induced by miR-29a-3p overexpression. This results is in agreement with previous studies which showed that activation of Wnt/β-catenin signaling facilitates tumor growth in lung cancer ( 40 ). The results showed that miR-29a-3p had a tumor suppressive role in NSCLC by restraining Wnt/β-catenin signaling.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…LiCl partially reversed the decrease in cell proliferation, invasion, and migration induced by miR-29a-3p overexpression. This results is in agreement with previous studies which showed that activation of Wnt/β-catenin signaling facilitates tumor growth in lung cancer ( 40 ). The results showed that miR-29a-3p had a tumor suppressive role in NSCLC by restraining Wnt/β-catenin signaling.…”
Section: Discussionsupporting
confidence: 94%
“…To further investigate the underlying mechanisms involved, the association between miR-29a-3p and Wnt/β-catenin signaling pathway in NSCLC was further examined next. The Wnt/β-catenin signaling pathway is required for numerous core biological processes, whilst also driving tumor initiation and progression ( 40 ). Wnt3a and β-catenin are Wnt signaling pathway-related proteins, that can enter the nucleus to regulate gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, overexpression of miRNA-15-5p abrogated nobiletin-mediated repression of β-catenin. These findings indicated that nobiletin inhibited WNT/βcatenin pathway mainly by downregulation of miRNA-15-5p in NSCLC (87).…”
Section: Regulation Of Mirnas By Nobiletinmentioning
confidence: 70%
“…Adriamycin is another drug that is listed which NSCLC has been found sensitized to when mimicking miR-138 [ 210 ]. As for picking antagomiRs, anti-miR-205, anti-miR-223 and anti-miR-15-5p resulted in sensitization of NSCLC to Cisplatin [ 211 ], Doxorubicin and Cisplatin [ 212 , 213 ] and Nobiletin [ 214 ], respectively. However, anti-miR-138-5p rather showed desensitization of NSCLC to Cisplatin implying that overexpression of miR-138-5p would retain chemosensitivity in NSCLC against the Platinum drug [ 215 ].…”
Section: Combination Of Mirna With Traditional Lung Cancer Therapymentioning
confidence: 99%